IC 9425 Multiple-Channel Trigger Circuit For Noise Discrimination In Ultrasonic Acoustic Emission Studies - David R. Hanson (The National Institute for Occupational Safety and Health (NIOSH), 1995)
Transient electrical noise events pose serious problems for data acquisition systems used in monitoring acoustic emissions in laboratory and field environments. The U.S. Bureau of Mines has designed and constructed a trigger discriminator circuit for use in ultrasonic acoustic emission studies. Designed for use with signals in the frequency range of 50 to 400 kHz, the instrument examines .incoming signals for frequency content, amplitude, simultaneity, threshold crossings, and number of channels above threshold. If preselected criteria on these properties are met, a plus 5-V pulse is output that may be used to trigger a data acquisition system, allowing rejection of noise events that do not possess useful information. The system was designed for four input channels, but may be expanded to more channels with minimal design changes.